2010
DOI: 10.1111/j.1365-2672.2009.04486.x
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR analysis of bacteriophage‐insensitive mutants (BIMs) of industrial Streptococcus thermophilus – implications for starter design

Abstract: Aims:  An efficient approach for generation of bacteriophage‐insensitive mutants (BIMs) of Streptococcus thermophilus starters was described in our laboratory [Mills et al. (2007) J Microbiol Methods70, 159–164]. The aim of this study was to analyse the phage resistance mechanism responsible for BIM formation. Methods and Results:  Three clustered regularly interspaced short palindromic repeat (CRISPR) regions have been identified in Strep. thermophilus, and Strep. thermophilus can integrate novel spacers into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 53 publications
1
47
0
1
Order By: Relevance
“…It has recently been shown that organisms with CRISPR sequence elements derived from a known phage or conjugative plasmid are resistant to infection by that phage or plasmid (Barrangou et al 2007;Brouns et al 2008;Deveau et al 2008;Sontheimer 2008, 2010b). Phage infection triggers the acquisition of invader-derived sequences by the host CRISPR locus via an unknown mechanism (Barrangou et al 2007;Deveau et al 2008;Mills et al 2009). Thus, the CRISPR-Cas system provides a defense that rapidly adapts to attacks on the host genome and has been shown to promote survival in natural microbial communities (Andersson and Banfield 2008;Tyson and Banfield 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that organisms with CRISPR sequence elements derived from a known phage or conjugative plasmid are resistant to infection by that phage or plasmid (Barrangou et al 2007;Brouns et al 2008;Deveau et al 2008;Sontheimer 2008, 2010b). Phage infection triggers the acquisition of invader-derived sequences by the host CRISPR locus via an unknown mechanism (Barrangou et al 2007;Deveau et al 2008;Mills et al 2009). Thus, the CRISPR-Cas system provides a defense that rapidly adapts to attacks on the host genome and has been shown to promote survival in natural microbial communities (Andersson and Banfield 2008;Tyson and Banfield 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The insensitive phenotype was initially attributed to nonspecific mutations in receptor genes. However, further studies revealed that phage insensitivity is due to alteration of the CRISPR (clustered regularly interspaced short palindromic repeats) locus, not associated with the previously thought mutations [142] (for further details on CRISPRs see section 6.5 and 12.4).…”
Section: Bim System -Exposure Of Sensitive Strains To Lytic Phages (Smentioning
confidence: 99%
“…Application of CRISPR/cas systems for construction of new LAB strain variants with differentiated resistance to phage infections is a novel alternative approach [67,142,156]. Moreover, such strains are regarded as safer for industrial applications, as the possibility for them to incorporate or disseminate foreign mobile genetic elements of unknown impact is low.…”
Section: Crispr/cas Defense In Labmentioning
confidence: 99%
“…Streptococcal genomes also harbor CRISPR/Cas systems of Types I and III with spacer identities suggesting that like Type II, they confer immunity against invading mobile elements (lytic and temperate phages, plasmids). 19,78,[88][89][90][91][92][93][94][95][96][97][98][99][100] To date, no other biological function than immunity against bacteriophages or plasmids has been assigned to CRISPR/Cas in streptococci.…”
Section: Integration Of Srnas Into the Regulatory Network Of Streptomentioning
confidence: 99%